PENGGUNAAN JAMUR ANTAGONIS Trichoderma sp. dan Gliocladium sp. UNTUK MENGENDALIKAN PENYAKIT LAYU FUSARIUM PADA TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Arie Ramadhina Arie Ramadhina; Lisnawita Lisnawita; Lahmuddin Lubis (Universitas Sumatera Utara, 2013)
The use of antagonism fungus of Trichoderma sp. and Gliocladium sp. for controlling wilt(Fusarium oxysporum) in red onion plants. The aim of the research was to know the effectiviness ofantagonism fungus of Trichoderma sp. and Gliocladium sp. in controlling wilt in red onion plants.The research used non-factorial RAK (random group design) with eight treatments: control, 10grams of F. oxysporum, 12 grams of Trichoderma sp., 18 grams of Trichoderma sp., 24 grams ofTrichoderma sp., and 12 grams of Gliocladium sp., 18 grams of Gliocladium sp., 24 grams ofGliocladium sp., and three repetitions. The result showed that the worst-highest disease was incontrol with 10 grams of F. oxysporum (2.60%) and the lowest disease was in control, 18 grams ofTrichoderma sp., 24 grams of Trichoderma sp., 18 grams of Gliocladium sp., and 24 grams ofGliocladium sp. (0.71%). The accident of the highest disease was in 10 grams of F. oxysporum(5.01%) and the lowest was in control, 18 grams of Trichoderma sp., 24 grams of Trichoderma sp.,18 grams of Gliocladium sp., and 24 grams of Gliocladium sp. (0.71%). The largest number ofleaves was in 24 grams of Trichoderma sp. (36 leaves), and the smallest was in 10 grams of F.oxysporum (29 leaves). The highest plants was in 24 grams of Gliocladium sp. (40.20 cm) and thelowest in 10 grams of F. oxysporum (37.26 cm). The largest number of F. oxysporum colonies in 10grams of F. oxysporum (8.86%). The highest production was in 24 grams of Trichoderma sp. (2.34tons/ha) and the lowest in 10 grams of F. oxysporum (1.56 tons/ha). The test of antagonism fungusof Trichoderma sp. and Gliocladium sp. on F. oxysporum indicates that the growth of both types ofantagonism is faster so that F. oxysporum tends to keep away from antagonism in the medium of thelaboratory.Keywords: Trichoderma sp., Gliocladium sp., Fusarium oxysporum, antagonism